From Landscape Architecture to Nature-Based Solutions: A Strategic Approach to Fine Dust Mitigation in Urban School Forests - Youngsun Seok; Kihwan Song; Jinhyung Chon; Yun Eui Choi (Land)
Urban areas face increasing environmental challenges, including fine dust pollution and climate change, which significantly impact public health and urban resilience. To address these issues, this study explores the integration of Nature-based Solutions (NbSs) and landscape architecture processes to develop a systematic approach for enhancing urban environmental outcomes. Through a comprehensive review of prior studies, the strengths and weaknesses of NbSs and landscape architecture processes were analyzed, leading to the development of the Nature-based Landscape Process (NLP), which synthesizes the key principles of both approaches. The Dongmyeong Elementary School Fine Dust Mitigation Forest Project was analyzed as a case study to evaluate the applicability of the NLP. This project, implemented using traditional landscape processes, was critically reviewed to identify areas where NbS principles could enhance ecological, social, and functional outcomes. The findings highlight how the integration of NbS principles into landscape architecture processes can address existing gaps and improve project sustainability and precision. This study provides practical insights into the application of the NLP in urban landscape projects, contributing to the development of strategies that align with long-term sustainability and climate adaptation goals.